Calcified Nanostructured Silicon Wafer Surfaces for Biosensing: Effects of Surface Modification on Bioactivity - Weis, Robert P. (IOS Press, 2002)
The growth of known biologically-relevant mineral phases on semiconducting surfaces is one strategy to explicitly induce bioactivity in such materials, either for sensing or drug delivery applications. In this work, we describe the use of a spark ablation process to fabricate deliberate patterns of Ca(10)(PO(4))(6)(OH)(2) on crystalline Si (calcified nanoporous silicon). These patterns have been principally characterized by scanning electron microscopy in conjunction with elemental characterization by energy dispersive x-ray analysis. This is followed by a detailed comparison of the effects of fibroblast adhesion and proliferation onto calcified nanoporous Si, calcified nanoporous Si derivatized with alendronate, as well as control samples of an identical surface area containing porous SiO(2). Fibroblast adhesion and proliferation assays demonstrate that a higher density of cells grow on the Ca(3)(PO(4))(2) /porous Si/ SiO(2) structures relative to the alendronate-modified surfaces and porous Si/SiOM(2) samples.